Predicting Transportation Outcomes for LEED Projects - Ewing, Reid; Greenwald, Michael J.; Zhang, Ming; Bogaerts, Meghan; Greene, William (Journal of planning education and research, 2013)
The article first estimates models of mode choice and average trip length for 239 diverse mixed-use developments in six diverse regions. It then applies these models to twelve Leadership in Energy and Environmental Design for Neighborhood Development (LEED-ND) pilot projects to predict approximate vehicle miles of travel (VMT) per person trip. Finally, it compares LEED-ND values to regional average values from the National Household Travel Survey. The VMT per person trip, for LEED-ND projects, ranges from 24 to 60 percent of the respective regional averages. The most urban and centrally located projects tended to achieve the highest alternative mode shares and the lowest private vehicle trip lengths.